RANCANG BANGUN SISTEM INFORMASI PELAYANAN JASA CUCI MOBIL BERBASIS WEB (STUDI KASUS: DULL CAR WASH) - Hidayat, Yanwar; Nugraha, Yopi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The rapid growth of digital technology has significantly shifted consumer behavior toward online shopping and service tracking, yet many small and medium enterprises (SMEs) still operate conventionally. Dull Car Wash, a local retail service business specializing in vehicle washing in Garut, faces operational constraints such as manual transaction recording, lack of real-time washing status information, and inefficient financial summaries. This study aims to design and develop a web-based service information system for Dull Car Wash using the Laravel framework and the Waterfall model. The system development encompasses requirements analysis, system design modeled with Unified Modeling Language (UML), and prototype creation. The resulting web application features a digital cashier system, real-time washing queue tracking, automatic employee commission calculation, and integrated financial reporting. The system design was validated through a structured review, demonstrating its capability to replace paper-based recording, minimize human errors in daily recapitulation, and provide centralized management dashboard for the business owner. This research delivers a software blueprint and responsive web prototype that enhances administrative efficiency and digital competitiveness for service-based automotive micro-enterprises.